Risk analysis and the security survey - Broder, James F.; Tucker, Eugene (Amsterdam ; Waltham, MA : Butterworth-Heinemann, 2012)
Security is an element of risk management, asserts James F. Broder in this edition of his classic Risk Analysis and the Security Survey. And he ably backs up that statement in this wonderfully written book, which should be required reading for all current and future security professionals.-
Includes bibliographical references and index.
oif 05/09/14
Loan
Keywords: Industries -- Security measures; Risk management; Crime prevention surveys; Assistance in emergencies -- Planning